Samson Raphael Hirsch's religious universalism and the German-Jewish quest for emancipation - Miller, Moshe Y. (Jews and Judaism: history and culture, 2024)
"In Samson Raphael Hirsch's Religious Universalism and the German-Jewish Quest for Emancipation Moshe Miller argues that nineteenth-century German Jews of all persuasions actively sought acceptance within German society and aspired to achieve full emancipation from the many legal strictures on their status as citizens and residents. But, where non-Orthodox Jews sought a large measure of cultural assimilation, Orthodox Jews were content with more delimited acculturation. However, they were no less enthusiastic about achieving emancipation and acceptance in German society. There was one issue, though, which was seen by non-Jewish critics of emancipation as a barrier to granting civic rights to Jews: namely, the alleged tribalism of the Jewish ethic and the supposedly Orthodox notion of Jews as "the Chosen People." These charges could not go unanswered, and in the writings of Rabbi Samson Raphael Hirsch (1808-1888), a leading thinker of the Orthodox camp, they did not. Hirsch stressed the universalism of the Jewish ethic and the humanistic concern for the welfare of all mankind, which he believed was one of the core teachings of Judaism. His colleagues in the German Orthodox rabbinate largely concurred with Hirsch's assessment. This account places Hirsch's views in their historical context and provides a detailed account of his attitude toward non-Jews and the Christianity practiced by the vast majority of nineteenth-century Europeans"--